Using Taylor vortices to create a film of nanoparticles for dip-coating. (August 2017) - Hof, Lucas A.; Rahman, Md. Masiar; Wüthrich, Rolf
Abstract: Taylor Couette flow is of importance for specific engineering applications like high-speed journal bearings. At the same time, nanoparticles thin film coating has attracted researchers to modify the surface properties of different substrates. Here, a novel and simple coating technology based on Taylor Couette flow is proposed, for coating a wide range of materials. Thin films of nanoparticles were created on the surface of a nanoparticle dispersion by Taylor vortex flow, allowing subsequent transfer of the films by dip-coating on various materials. Scaling laws were derived for the coating setup allowing its application for a wide range of sample sizes.